Live Birth After the Transfer of Embryos Obtained by Fertilization of Vitrified Oocytes. Report of One Case [Parto Tras la Transferencia de Embriones Generados por Fecundación de Ovocitos Vitrificados. Comunicación de Un Caso] - Schwarze-Meza, J (2011)
We report the first successful live birth after the transfer of embryos obtained by fertilization of vitrified oocytes. A couple with primary infertility due to teratozoospermy and chronic anovulation decided to undergo assisted reproductive technology after 4 failed cycles of superovulation and intrauterine insemination. The woman underwent a standard luteal phase agonist protocol, with controlled ovarian hyper stimulation with daily 150 IU recombinant gonadotropin and 75 IU urinary gonadotropin for 12 days. Due to the high risk of ovarian hyper stimulation syndrome the couple was advised to delay embryo transfer. Eighteen mature oocytes were recovered, eight were vitrifi ed and 10 fertilized and cryopreserved as pro-nuclei. Two months later, four vitrifi ed oocytes were thawed, and three morphologically-normal embryos were transferred to an estrogen-progesterone-primed uterus, obtaining a triple clinical pregnancy. The pregnancy was uneventful until 32 weeks of amenorrhea, when preterm delivery started. After inducing lung maturity, a cesarean section was performed and three healthy fetuses were delivered. Nowadays, the babies are two and a half years old, and have had a normal psycho-motor development.